2016
DOI: 10.1097/gme.0000000000000532
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in midlife women in Qatar

Abstract: Objective The prevalence of osteoarthritis (OA) and rheumatoid arthritis (RA) has been poorly documented in the Middle East and North African region, including the State of Qatar. Given that musculoskeletal pain is commonly reported among midlife women, we evaluated the association between self-report of either OA or RA and health-related quality of life (HRQoL) among midlife women in Qatar. Additionally, HRQoL among women in Qatar was compared to that of women in the Study of Women Across the Nation (SWAN). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, the individual studies included in that analysis (all conducted prior to 1982) evaluated heterogeneous populations and reported prevalence rates of 0.91–5.71%, with higher rates associated with older study populations [ 12 ]. One study of women visiting primary health centers in Qatar identified a prevalence of 4.3%, but again, all patients were 40–60 years of age and the presence or absence of RA was self-reported rather than determined by an investigator [ 14 ]. Aside from these exceptions, the majority of studies reported prevalence rates below 1%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the individual studies included in that analysis (all conducted prior to 1982) evaluated heterogeneous populations and reported prevalence rates of 0.91–5.71%, with higher rates associated with older study populations [ 12 ]. One study of women visiting primary health centers in Qatar identified a prevalence of 4.3%, but again, all patients were 40–60 years of age and the presence or absence of RA was self-reported rather than determined by an investigator [ 14 ]. Aside from these exceptions, the majority of studies reported prevalence rates below 1%.…”
Section: Resultsmentioning
confidence: 99%
“…This could explain the low prevalence found for this region, where robust data sources for some countries are limited. On the other hand, many of the publications reporting county-level prevalence of RA are based on self-reported data from small regions [ 14 , 15 , 17 , 21 , 22 , 24 ], which may also result in skewed estimates. This uncertainty may be reflected in secular trends, too.…”
Section: Discussionmentioning
confidence: 99%
“…As the major part of weight-bearing peripheral joint, the knee is the most frequently affected site [ 2 ]. The structural changes result in pain, stiffness, swelling, and tenderness and then reduce physical function and affect the quality of life of patients [ 3 ]. About 10–13% of the causes of disability for people aged 60 years and above are attributable to knee osteoarthritis (KOA) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not examine the prevalence of symptoms in relation to BMI 30 . The SWIQ collected data from a more diverse group in Qatar and found that most women aged 40 to 60 yr (71.6%) reported being bothered by aches and stiffness in joints within the past 2 weeks 31 . In addition, BMI was positively associated with the odds of reduced physical function (OR, 1.07; 95% confidence interval [CI], 1.04-1.11), increased bodily pain (OR, 1.04; 95% CI, 1.02-1.07), reduced social function (OR, 1.03; 95% CI, 1.00-1.05), and reduced emotional and psychological status (OR, 1.03; 95% CI, 1.01-1.06) 31 .…”
mentioning
confidence: 99%
“…The SWIQ collected data from a more diverse group in Qatar and found that most women aged 40 to 60 yr (71.6%) reported being bothered by aches and stiffness in joints within the past 2 weeks 31 . In addition, BMI was positively associated with the odds of reduced physical function (OR, 1.07; 95% confidence interval [CI], 1.04-1.11), increased bodily pain (OR, 1.04; 95% CI, 1.02-1.07), reduced social function (OR, 1.03; 95% CI, 1.00-1.05), and reduced emotional and psychological status (OR, 1.03; 95% CI, 1.01-1.06) 31 . In a recent study of sleep in Qatar, obese individuals had higher odds of sleeping less than 7 hours per night (OR, 1.58, 95% CI, 1.06-2.35) compared with individuals of healthy weight after adjusting for sociodemographic variables 32 …”
mentioning
confidence: 99%